Cyclic guanosine monophosphate modulates locomotor acceleration induced by nitric oxide but not serotonin in Clione limacina central pattern generator swim interneurons ... - Pirtle, Thomas; Satterlie, Richard (Dryad, 2020)
Typically, the marine mollusk, Clione limacina, exhibits a slow, hovering locomotor gait to maintain its position in the water column. However, the animal exhibits behaviorally relevant locomotor swim acceleration during escape response and feeding behavior. Both nitric oxide and serotonin mediate this behavioral swim acceleration. In this study, we examine the role that the second messenger, cGMP, plays in mediating nitric oxide and serotonin induced swim acceleration. We observed that application of an analogue of cGMP or an activator of soluble guanylyl cyclase, increased fictive locomotor speed recorded from Pd-7 interneurons of the animal’s locomotor central pattern generator. Moreover, inhibition of soluble guanylyl cyclase decreased fictive locomotor speed. These results suggest that basal levels of cGMP are important for slow swimming and that increased production of cGMP mediates swim acceleration in Clione. Because nitric oxide has its effect through cGMP signaling and because we show herein that ... : Data collected represent intracellular recordings from Pd-7 interneurons of the Clione limacina locomotor central pattern generator using Axon Instruments Axoclamp 2B or A-M Systems amplifiers with thin-walled borosilicate glass microelectrodes filled with 2 M potassium acetate. Data are representative of recordings made using Axon Instruments, Inc. Axoscope software or Pclamp software and A/D converter connected to a PC computer. Action potential frequency (an indication of fictive swim frequency), action potential duration, and sag potential amplitude were measured in control conditions and after application of pharmacological agents (drugs that affect nitric oxide signaling and cGMP signaling). Statistical analysis of the mean control values to mean experimental values are compared and was done using GraphPad Instat (GraphPad Software, La Jolla, CA, USA). ...